Dinamika Sosial Kehidupan Multikultural di Kota Medan Era Kontemporer - Wandini, Putri; Rivaldi, Alvin; Siregar, Yusra Dewi (Medan Resource Center, 2024)
Medan, a prominent multicultural city in Indonesia, has long served as a center of interethnic interactions, tracing back to the Sultanate of Deli and continuing into the modern era. This study investigates how Medan's multicultural life shapes the city’s social identity and examines the contributions of various communities to its social, economic, and cultural dynamics. Employing a qualitative literature analysis, the research explores the experiences and perspectives of Malay, Chinese, Batak, and Indian ethnic groups across domains such as art and economy. Findings reveal that, despite challenges and differences, harmony is maintained through tolerance and respect for cultural diversity. This conclusion underscores the significance of interethnic collaboration in preserving unity amidst diversity as the foundation of Medan’s multicultural existence.